Outage Performance of a SIMO HP-DF Cooperative Multi-hop Network - Tastan, Mustafa Cihan; Ilhan, Haci; Aygolu, Umit (IEEE, 2017)
In this paper, a cooperative multi-hop relaying network is proposed for single-input multiple-output (SIMO) links. The system involves the high performance decode-and forward (HP-DF) cooperative communication technique to provide diversity in fixed DF relaying. The outage probability and the diversity order of the proposed system is analytically derived for Rayleigh fading channels and it is shown that the asymptotic diversity order is doubled compared to the noncooperative case and that the number of hops has no effect on the diversity order which is equal to two times the number of receive antennas. Theoretical results are supported via computer simulations for several number of receive antennas as well as for several number of hops.
Keywords: MIMO system; cooperative communications; multi-hop networks; Computer Science; Engineering; Telecommunications